Moving from Batch to Continuous Operation for the Liquid Phase Dehydrogenation of Tetrahydrocarbazole - Shen, Y.; Ma'amor, A.; Abu-Dharieh, J.; Thompson, J.M.; Kalirai, B.; Stitt, E.H.; Rooney, D.W. (American Chemical Society, 2014)
Despite the numerous advantages of continuous processing, high-value chemical production is still dominated by batch techniques. In this paper, we investigate options for the continuous dehydrogenation of 1,2,3,4-tetrahydrocarbazole using a trickle bed reactor operating under realistic liquid velocities with and without the addition of a hydrogen acceptor. Here, a commercial 5 wt % Pd/Al2O3 catalyst was observed to slowly deactivate, hence proving unsuitable for continuous use. This deactivation was attributed to the strong adsorption of a byproduct on the surface of the support. Application of a base washing technique resolved this issue and a stable continuous reaction has been demonstrated. As was previously shown for the batch reaction, the addition of a hydrogen acceptor gas (propene) can increase the overall catalytic activity of the system.